New species of Thinophilus Wahlberg (Diptera: Dolichopodidae) from mangroves in southern China (Shenzhen) - Grootaert, Patrick; Tang, Chufei; Yang, Ding (Zootaxa, 2015)
Three species of Thinophilus Wahlberg are recorded from mangroves near Shenzhen (China). Two species new to science are described and illustrated: T. dongae sp. nov. and T. zhuae sp. nov. In addition, Thinophilus lamellaris Zhu, Yang & Masunaga originally described from Hainan (China) is reported here. Females of this species are described for the first time and variability in male characters is given. These three species plus 6 additional Thinophilus and three Nanothinophilus species from South China Sea mangroves were COI barcoded and compared to species known from the northern part of the South China Sea.